Պաշտոնական նամակագրությունը և դիվանագիտական ընծաները հայ-մոնղոլական հարաբերություններում - Դանիելյան, Գագիկ (Մատենադարան)
Мамлюкскиe канцелярские руководства и административные энциклопедии – отнюдь не единственные источники для изучения официальной переписки между Киликийской Арменией и соседними нехристианскими государствами. До нас дошел еще один важный источник XIV века, который дает некоторое представление о протоколе дипломатической переписки правящих кругов монгольского Ильханата Ирана с армянскими царями Киликии, а также с армянскими католикосами и духовенством. Это – «Дастур аль-катиб фи таʿйин аль-маратиб», канцелярский справочник, написанный на персидском языке Мухаммадом ибн Хиндушахом Нахчивани (ум. в 1376 г.), также известным под прозвищем Шамс Мунши. The Mamluk chancellery manuals and administrative encyclopedias are not the only sources for the study of the official correspondence between Cilician Armenia and neighboring non-Christian powers. Another important source has come down to us from the 14th century. It yields some insights into the protocol of diplomatic correspondence between the ruling authorities of the Mongol Ilkhanate of Iran and the Armenian kings of Cilicia, as well as the Armenian catholicoi and clergy. That source is Dastūr al-kātib fī taʿyīn almarātib, a chancellery handbook written in Persian by Muḥammad ibn Hindušāh Naḫğawānī (d. 1376) also known under the nickname of Šams Munšī.
Keywords: Պատմություն